Family roles of working mothers in the San Nicolás neighborhood of the San Juan del Paraná district who work at the Encarnación - Posadas border crossing (UNIHumanitas, 2020)
This research focuses on describing the role of working mothers in the San Nicolás neighborhood, District of San Juan del Paraná, who work in the Encarnación, Paraguay-Posadas, Argentina border crossing. This research topic has been considered in view of the growing phenomenon of mothers who are dedicated to the transfer of goods to the Argentine side, Many of them are inhabitants of the District of San Juan del Paraná (Encarnación-Paraguay) and there is a need to describe the roles of working mothers, since this is a job with no fixed timetable for entry or exit. The research is framed within a qualitative methodological design, of an exploratory-descriptive type, the research technique used responds to the interview applied to five mothers who work at the border crossing, from the results obtained it was possible to dimension the role of these and thus better understand the meaning and orientation that the work with the family acquires both for them and for all their domestic units. Thus, the main contribution of this document was the description of the family and work role from a gender perspective.
Keywords: woman; work; family; genre